Fucoidan Rescues p-Cresol-Induced Cellular Senescence in Mesenchymal Stem Cells via FAK-Akt-TWIST Axis - Jun Hee Lee; Chul Won Yun; Jin Hur; Sang Hun Lee (Marine Drugs, 2018)
Mesenchymal stem cells (MSCs) are a source for cell-based therapy. Although MSCs have the potential for tissue regeneration, their therapeutic efficacy is restricted by the uremic toxin, p-cresol, in chronic kidney disease (CKD). To address this issue, we investigated the effect of fucoidan, a marine sulfated polysaccharide, on cellular senescence in MSCs. After p-cresol exposure, MSC senescence was induced, as indicated by an increase in cell size and a decrease in proliferation capacity. Treatment of senescent MSCs with fucoidan significantly reversed this cellular senescence via regulation of SMP30 and p21, and increased proliferation through the regulation of cell cycle-associated proteins (CDK2, CDK4, cyclin D1, and cyclin E). These effects were dependent on FAK-Akt-TWIST signal transduction. In particular, fucoidan promoted the expression of cellular prion protein (PrPC), which resulted in the maintenance of cell expansion capacity in p-cresol-induced senescent MSCs. This protective effect of fucoidan on senescence-mediated inhibition of proliferation was dependent on the TWIST-PrPC axis. In summary, this study shows that fucoidan protects against p-cresol-induced cellular senescence in MSCs through activation of the FAK-Akt-TWIST pathway and suggests that fucoidan could be used in conjunction with functional MSC-based therapies in the treatment of CKD.